2013
DOI: 10.3945/jn.113.175075
|View full text |Cite
|
Sign up to set email alerts
|

Iron Bioavailability from a Lipid-Based Complementary Food Fortificant Mixed with Millet Porridge Can Be Optimized by Adding Phytase and Ascorbic Acid but Not by Using a Mixture of Ferrous Sulfate and Sodium Iron EDTA

Abstract: Home fortification with lipid-based nutrient supplements (LNSs) is a promising approach to improve bioavailable iron and energy intake of young children in developing countries. To optimize iron bioavailability from an LNS named complementary food fortificant (CFF), 3 stable isotope studies were conducted in 52 young Beninese children. Test meals consisted of millet porridge mixed with CFF and ascorbic acid (AA). Study 1 compared iron absorption from FeSO4-fortifed meals with meals fortified with a mixture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 41 publications
1
19
0
1
Order By: Relevance
“…The mineral content of both formulations were high, the lower extractabilities for both zinc and iron of red amaranth composite (RSG) were probably due to high content of fibre (3.9) in them than in OFSP composite (OSG) as shown in Table 11. High Fiber in foods hinders bioavailability of minerals such as zinc and iron [41] [42] [43]. The mineral content of the formulations was similar to that reported by [40].…”
Section: Mineral Content and Extractabilities Of The Most Acceptable supporting
confidence: 63%
“…The mineral content of both formulations were high, the lower extractabilities for both zinc and iron of red amaranth composite (RSG) were probably due to high content of fibre (3.9) in them than in OFSP composite (OSG) as shown in Table 11. High Fiber in foods hinders bioavailability of minerals such as zinc and iron [41] [42] [43]. The mineral content of the formulations was similar to that reported by [40].…”
Section: Mineral Content and Extractabilities Of The Most Acceptable supporting
confidence: 63%
“…In young Beninese children, iron absorption from a lipid‐based complementary food mixed with millet porridge and fortified with a mixture of NaFeEDTA and FeSO 4 was significantly lower than from meals fortified with FeSO 4 only (Cercamondi et al . ). The authors explained this rather surprising outcome by the possibility that the ascorbic acid provided enhanced absorption of FeSO 4 but not NaFeEDTA.…”
Section: Discussionmentioning
confidence: 97%
“…However, this aspect warrants more attention, because we usually have meals as a combination of several dishes or foods and interactions between nutrients must have an effect on our health condition (21,22). Some other studies reported the portion sizes among children for a limited number of foods (23,24).…”
Section: Discussionmentioning
confidence: 99%